1995
DOI: 10.1063/1.360106
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency noise measurements of AlxGa1−xAs/InyGa1−y As/GaAs high electron mobility transistors

Abstract: Low-frequency noise measurements have been performed in the linear range of the I-V characteristics of pseudomorphic Al0.3Ga0.7As/In0.25Ga0.75As/GaAs high electron mobility transistors (HEMTs) grown by molecular beam epitaxy with different channel thicknesses. The results obtained show that the 1/f noise in such devices depends greatly on channel thickness. It is controlled by the penetration of the electron wavefunction into the barrier as well as by Coulombic effects for thin channels and by the increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Such dependencies are used very often to discuss and analyze the peculiarities of the 1 / f noise in MODFETs. 9,11,15,32 In short channel HEMTs with the high ratio L c / L g , ͑L c is the channel length͒, the spectral noise density S I / I d 2 is often independent or weakly dependent on the gate voltage at voltages close to zero gate bias. 9,15,32 That is because the resistance of the gated part of the channel at V g Ϸ 0͑V gn Ϸ 1͒ is only a small fraction of the total drain to source resistance and noise is mainly determined by the ungated part of the channel and the contacts.…”
Section: -3mentioning
confidence: 99%
See 2 more Smart Citations
“…Such dependencies are used very often to discuss and analyze the peculiarities of the 1 / f noise in MODFETs. 9,11,15,32 In short channel HEMTs with the high ratio L c / L g , ͑L c is the channel length͒, the spectral noise density S I / I d 2 is often independent or weakly dependent on the gate voltage at voltages close to zero gate bias. 9,15,32 That is because the resistance of the gated part of the channel at V g Ϸ 0͑V gn Ϸ 1͒ is only a small fraction of the total drain to source resistance and noise is mainly determined by the ungated part of the channel and the contacts.…”
Section: -3mentioning
confidence: 99%
“…That is the reason why the low frequency noise in InGaAs-based MODFETs has been extensively studied. [6][7][8][9][10][11][12][13][14] Nevertheless, the understanding of the noise mechanisms is incomplete.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, LFN in HEMTs is one of the major limitations on the performance of high-frequency analog circuits. 2) Numerous studies [3][4][5][6][7][8][9][10][11][12] on LFN have been reported. In the context of LFN in homogeneous III-V compound semiconductors, Hooge has proposed an empirical relation, 3) in which the spectrum density of the noise [S n ð f Þ] is inversely proportional to the total number of carriers (N) and proportional to the square of current (I) through the sample.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that these exist some types of noise source. With respect to LFN in HEMTs, some possible noise sources have been suggested: the mobility fluctuation [3][4][5] mentioned above, generation-recombination (g-r) noise arising from deep levels in AlGaAs, 6) multiple g-r noise in the channel, 7) gate leakage current noise, 8) channel roughness and penetration of the electron wave function, 9) leakage current through the semi-insulating substrate 10,13) and surface g-r noise. 11) Furthermore, Nishiyama and Higuchi succeeded in separating LFN into three noise sources that are located in the intrinsic, source and drain regions.…”
Section: Introductionmentioning
confidence: 99%